Identifying and Characterizing a Novel Peritrophic Matrix Protein (MdPM-17) Associated With Antibacterial Response From the Housefly, Musca domestica (Diptera: Muscidae). Issue 6 (21st December 2020) - Wang, Yu; Cheng, Jinzhi; Luo, Man; Wu, Jianwei; Guo, Guo
Abstract: Peritrophic matrix/membrane (PM) critically prevents the midgut of insects from external invasion by microbes. The proteins in the peritrophic membrane are its major structural components. Additionally, they determine the formation and function of this membrane. However, the role of PM proteins in immune regulation is unclear. Herein, we isolated a novel PM protein ( Md PM-17) from Musca domestica larvae. Further, the function of Md PM-17 in regulating host innate immunity was identified. Results showed that the cDNA of Md PM-17 full is 635 bp in length. Moreover, it consists of a 477-bp open reading frame encoding 158 amino acid residues. These amino acid residues are composed of two Chitin-binding type-2 domain (ChtBD2) and 19 amino acids as a signal peptide. Moreover, tissue distribution analysis indicates that Md PM-17 was enriched expressed in midgut, and moderate levels in the fat body, foregut, and malpighian tubule. Notably, Md PM-17 recombinant protein showed high chitin-binding capacity, thus belongs to the Class III PM protein group. Md PM-17 protein silencing via RNA interference resulted in the expression of antimicrobial peptide (defensin, cecropins, and diptericin) genes, and this occurred after oral inoculation with exogenous microbes Escherichia coli (Enterobacteriales:Enterobacteriaceae), Staphylococcus aureus (Bacillales:Staphylococcaceae), and Candida albicans (Endomycetales:Saccharomycetaceae)). Therefore, all the antimicrobial peptide (AMP) gene expression levels are high in Md PM-17-depleted larvae during microbial infection compared to controls. Consequently, these findings indicate that Md PM-17 protein is associated with the antibacterial response from the housefly.